If,

Sachin + Ramesh + Tendulkar = 6

Sachin x Ramesh = 2

Ramesh x Tendulkar = 6

Then,

Tendulkar x Sachin =?

3

Sachin + Ramesh + Tendulkar = 6
Sachin x Ramesh = 2
Ramesh x Tendulkar = 6

Given.
Sachin x Ramesh = 2
Ramesh x Tendulkar = 6

Rewriting Both equations in terms of Ramesh,
Sachin = 2/Ramesh
Tendulkar = 6/Ramesh

Replacing above values in equation "Sachin + Ramesh + Tendulkar = 6"
2/Ramesh + Ramesh + 6/Ramesh =6
(2 + Ramesh^2 + 6)/Ramesh = 6
8 + Ramesh^2 = 6Ramesh
Ramesh^2 - 6Ramesh + 8 = 0
(Ramesh - 4) (Ramesh - 2) = 0

Therefore;
Ramesh = 4 or 2

Let us take value of Ramesh as 2
Sachin = 2/2 = 1
Tendulkar = 6/2 = 3

Therefore;
Tendulkar x Sachin = 3 x 1 = 3

Discussion